2006
DOI: 10.1007/s10886-006-9104-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Wind Speed on the Pheromone-Mediated Behavior of Sexual Morphs of the Potato Aphid, Macrosiphum euphorbiae (Thomas) Under Laboratory and Field Conditions

Abstract: The effect of wind on the potato aphid, Macrosiphum euphorbiae, male responsiveness to the sex pheromone, and on the calling behavior of virgin oviparae, was studied under constant wind speeds in the laboratory and in the field. A significant proportion of females called at wind speeds up to 4 m/sec, whereas male flight behavior in clean air was inhibited at velocities > 2 m/sec. However, males continued to walk over the range of wind speeds at which females called. Under constant wind velocities in a wind tun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 37 publications
3
19
0
Order By: Relevance
“…). However, aphids are generally not attracted to plants via volatile cues at this range due to an inability to orient while in flight (Nottingham & Hardie ; Goldansaz & McNeil ; reviewed in Powell, Tosh & Hardie ; Webster ). In contrast, both alate and apterous aphids make extensive use of volatile foraging cues when walking (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…). However, aphids are generally not attracted to plants via volatile cues at this range due to an inability to orient while in flight (Nottingham & Hardie ; Goldansaz & McNeil ; reviewed in Powell, Tosh & Hardie ; Webster ). In contrast, both alate and apterous aphids make extensive use of volatile foraging cues when walking (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is not unreasonable to think that males also respond to the changes in atmospheric pressure for the same reasons suggested for females. Winged male are very poor fliers and flight initiation is inhibited at low windspeeds [39], so once blown off the plant they would have little chance to relocate overwintering hosts with receptive oviparae.…”
Section: Discussionmentioning
confidence: 99%
“…Winged morphs are also produced on the secondary host in response to overcrowding (Sutherland, 1969). Aphids are relatively weak flyers and will not attempt to fly unless wind speeds are fairly low (Kennedy, 1990; Hardie et al , 1996; Goldansaz & McNeil, 2006), but wind tunnel experiments have shown that flying aphids are capable of making targeted landings on plants or leaf‐sized yellow or green targets under low wind conditions (Storer et al , 1999; Vargas et al , 2005; Goldansaz & McNeil, 2006).…”
Section: Types Of Olfactory‐mediated Behaviourmentioning
confidence: 99%
“…Because of their weak flying ability (Kennedy, 1990; Hardie et al , 1996), walking may be a safer and more reliable way of travelling short distances. Sexual males of Macrosiphum euphorbiae will preferentially walk towards the odour of a nearby calling females rather than fly, when presented with a wire path to walk along, if wind speeds are above 2 m s −1 (Goldansaz & McNeil, 2006). Summer migrants quickly lose the ability to fly after landing on a new host as a result of autolysis of the flight muscles.…”
Section: Types Of Olfactory‐mediated Behaviourmentioning
confidence: 99%